Prostaglandin E2 dependent migration of human brain endothelial cells is mediated through Rho-Kinase-II - Gausal Azam Khan; Arjun Ghosh (PLoS ONE, 2025)
Prostaglandin E2 (PGE2), that plays a crucial role in angiogenesis as well as in ischemic and inflammatory disorders of the brain, is associated with breakdown of the blood-brain barrier (BBB). Previously, we had shown that PGE2-induced human brain endothelial cells (HBECs) migration, and works in a cooperative manner through its three receptors (EP2, EP3 & EP4). However, the detailed signaling mechanism of PGE2-induced HBECs migration remains obscure. In this present study, we investigated the signaling pathway of actin dynamics/polymerization and migration of HBECs by PGE2 in vitro. Expression of ROCK was analyzed by ELISA and RT-PCR. Actin polymerization was evaluated by NBD-phallacidin immunofluorescence staining. HBECs expressed only ROCK II. PGE2 (100 pM) induced ROCK II expression occurs in dose-and-time-dependent manner. ROCK II inhibition by Y27632 (150nM), as well as ROCK II silencing significantly attenuated PGE2-induced migration of HBECs. We further showed that pretreatment of PKA inhibitor (H-89; 0.5 μM) or adenylate cyclase inhibitor (ddA; 1μM) completely inhibited PGE2-induced ROCK II activity. Furthermore, PGE2-induced MLC phosphorylation also occurs in a time-dependent manner. However, pretreatment of ROCK II inhibitor or silencing of ROCK II significantly abrogated PGE2-induced MLC phosphorylation as well as F-actin polymerization. Our ex-vivo aortic ring angiogenesis study also showed that pretreatment of ROCK II inhibitor significantly inhibited ECs sprouting. These results suggest that PGE2-induced HBECs migration is mediated through PKA, ROCK II and MLC phosphorylation as well as F-actin polymerization, indicating that modulation of these pathways may aid in the future treatment of dysregulated angiogenesis in cerebrovascular diseases.